PHO1 family members transport phosphate from infected nodule cells to bacteroids in Medicago truncatula. Issue 1 (25th November 2020) - Nguyen, Nga N T; Clua, Joaquin; Vetal, Pallavi V; Vuarambon, Dominique Jacques; De Bellis, Damien; Pervent, Marjorie; Lepetit, Marc; Udvardi, Michael; Valentine, Alexander J; Poirier, Yves
Abstract: Legumes play an important role in the soil nitrogen availability via symbiotic nitrogen fixation (SNF). Phosphate (Pi) deficiency severely impacts SNF because of the high Pi requirement of symbiosis. Whereas PHT1 transporters are involved in Pi uptake into nodules, it is unknown how Pi is transferred from the plant infected cells to nitrogen-fixing bacteroids. We hypothesized that Medicago truncatula genes homologous to Arabidopsis PHO1, encoding a vascular apoplastic Pi exporter, are involved in Pi transfer to bacteroids. Among the seven MtPHO1 genes present in M. truncatula, we found that two genes, namely MtPHO1.1 and MtPHO1.2, were broadly expressed across the various nodule zones in addition to the root vascular system. Expressions of MtPHO1.1 and MtPHO1.2 in Nicotiana benthamiana mediated specific Pi export. Plants with nodule-specific downregulation of both MtPHO1.1 and MtPHO1.2 were generated by RNA interference (RNAi) to examine their roles in nodule Pi homeostasis. Nodules of RNAi plants had lower Pi content and a three-fold reduction in SNF, resulting in reduced shoot growth. Whereas the rate of 33 Pi uptake into nodules of RNAi plants was similar to control, transfer of 33 Pi from nodule cells into bacteroids was reduced and bacteroids activated their Pi-deficiency response. Our results implicate plant MtPHO1 genes in bacteroid Pi homeostasis and SNF via the transfer of Pi from nodule infected cells to bacteroids. Abstract : Two members of the PHO1 family in Medicago truncatula are involved in the transport of phosphate from the infected nodule cells to the Sinorhizobium meliloti bacteroids.